2018
DOI: 10.1111/echo.13886
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of left atrial active function measured by speckle tracking echocardiography in patients with hypertrophic cardiomyopathy

Abstract: Loss of LA active function was associated with increased cardiac events in patients with HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
(40 reference statements)
3
19
0
1
Order By: Relevance
“…The data from literature indicate the potential usefulness of the speckle tracking technique in predicting the cardiac events among HCM patients. For example Fujimoto et al proved that LA peak longitudinal strain <20.3% is associated with an increased risk of heart failure and atrial fibrillation in the follow up [17,25]. A similar observation was also presented by the other authors [4,10,15].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The data from literature indicate the potential usefulness of the speckle tracking technique in predicting the cardiac events among HCM patients. For example Fujimoto et al proved that LA peak longitudinal strain <20.3% is associated with an increased risk of heart failure and atrial fibrillation in the follow up [17,25]. A similar observation was also presented by the other authors [4,10,15].…”
Section: Discussionsupporting
confidence: 57%
“…Comparison of clinical and echocardiographic parameters in... Two-and four-chamber apical views were determined by finding the largest long-axis. Due to the absence of an LA-specific software, we used software dedicated to LV analysis as described in the literature [15,17].…”
Section: Speckle Tracking Parametersmentioning
confidence: 99%
“…However, in contrast to the Kowallick’s study, the LA booster pump function in our study was not statistically different between the NOHCM patients and the normal controls. The LA booster pump functions in previous HCM patient studies in the literature has not been consistent and has been separately reported as normal [30], increased [21] or reduced [12]. LA contraction is influenced by pulmonary venous return (atrial pre-load), LV end-diastolic pressure (atrial after-load), and LV systolic reserve [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, analysis of the LA functional parameters of strain and strain rate (SR) using non-invasive imaging modalities such as echocardiography speckle tracking (STE) and cardiovascular magnetic resonance (CMR) feature tracking (CMR-FT) have been proposed for further evaluation. STE has been proven to be a feasible and reproducible technique to evaluate LA function [11] and has demonstrated significant LA function impairment in HCM [1214]. CMR-FT is a new quantitative method for wall motion assessment that is analogous to STE [15].…”
Section: Introductionmentioning
confidence: 99%
“…20) In HCM patients, Fujimoto, et al have shown that loss of LA active function (evaluated by LA strain) was independently associated with increased cardiac events. 21) When recent insights about LA physiology and function are taken together, it creates a paradigm shift that the LA is no longer simply being a passive marker of disease severity, but an active component of the heart failure in HCM patients. Several questions still remain to be answered.…”
mentioning
confidence: 99%